Clinical case of secondary osteoporosis in patient with ulcerative colitis - L. V. Zhuravlyova; Yu. K. Sikalo; M. O. Oliinyk (Zaporozhye State Medical University, 2020)
The incidence and prevalence of chronic inflammatory diseases of the gastrointestinal tract has been steadily increasing recently in all regions of the world. Celiac disease, Crohn's disease and non-specific ulcerative colitis, among others, are diagnosed during the most productive period of life, which significantly limits its quality, as well as violate the patient's psycho-emotional state and social status. Among the intestinal manifestations of chronic diseases of the small and large intestine, the osteoporosis is most relevant, and associated with an increased risk of fractures. Aim. To describe the clinical case of secondary osteoporosis in patient with a long course of nonspecific ulcerative colitis, to cover the problem of monitoring, treatment and possible solutions. Results. The clinical case of development of severe secondary osteoporosis in a patient with non-specific ulcerative colitis is presented. Determinants of bone loss in this category of patients are chronic inflammation of the mucous membrane, impaired enteral absorption and glucocorticoid therapy. Current risk monitoring tools for osteoporosis in risk groups are the determination of individual risk of fractures FRAX®, regular clinical laboratory monitoring and densitometry. Current treatment of secondary osteoporosis should be personalized with proper control over the course of the underlying disease. Conclusion. The described clinical case demonstrates a need for further population-based prospective studies to create diagnostic and therapeutic algorithms. These algorithms could help provide personalized therapy to patients with gastrointestinal diseases in group of osteoporosis and fractures risk at a young age.